2016
DOI: 10.3899/jrheum.160493
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Myocarditis: Initial Presentation and Longterm Outcomes in a Multicentric Series of 29 Patients

Abstract: LM is a severe manifestation of SLE. It can be the first manifestation of the disease or it can occur during followup, in particular in untreated patients. However, the longterm prognosis is typically positive. Patients with less severe disease exhibited good LVEF recovery without CYC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 33 publications
5
70
0
6
Order By: Relevance
“…It can be the initial cardiac manifestation during the progression of SLE in, particularly, among the untreated patients [32]. A French study showed that myocarditis was the first symptom in 58.6% of SLE patients [33], while 5.7% of Chinese SLE patients suffered from myocarditis in our study. Steroids and cyclophosphamide provide therapy for lupus myocarditis [34,35].…”
Section: Discussionsupporting
confidence: 45%
“…It can be the initial cardiac manifestation during the progression of SLE in, particularly, among the untreated patients [32]. A French study showed that myocarditis was the first symptom in 58.6% of SLE patients [33], while 5.7% of Chinese SLE patients suffered from myocarditis in our study. Steroids and cyclophosphamide provide therapy for lupus myocarditis [34,35].…”
Section: Discussionsupporting
confidence: 45%
“…Previous reports showed that prevalence of lupus myocarditis is 5–10% of patients [ 3 , 4 ], and mortality may be as high as 10.3% according to a large case series from Paris [ 6 ]. Although other studies report that concomitant lupus activity in various organ occurs in 97% of the patients with lupus myocarditis [ 7 ], our report provides a rare evidence that lupus myocarditis may be a sole manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be the first manifestation of the disease or it can occur during the follow up, in particular in untreated patients (33). In a recent French series of 29 lupus myocarditis, myocarditis was the first sign of SLE in 58.6% of cases (34). The CMR revealed delayed gadolinium enhancement in 9/13 (69%) patients.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%